Thermal properties of molecular crystals through dispersion-corrected quasi-harmonic ab initio calculations: the case of urea. Issue 9 (15th December 2015) - Erba, Alessandro; Maul, Jefferson; Civalleri, Bartolomeo
Abstract : A multifaceted ab initio theoretical framework is presented for computing the thermal (structural, elastic, thermodynamic) properties of molecular crystals. Abstract : An ab initio quantum-mechanical theoretical framework is presented to compute the thermal properties of molecular crystals. The present strategy combines dispersion-corrected density-functional-theory (DFT-D), harmonic phonon dispersion, quasi-harmonic approximation to the lattice dynamics for thermal expansion and thermodynamic functions, and quasi-static approximation for anisotropic thermo-elasticity. The proposed scheme is shown to reliably describe thermal properties of the urea molecular crystal by a thorough comparison with experimental data.